Advances in personalized therapy for lung cancer. (September 2013) - Kim, Eric S; Pandya, Kishan J
Abstract : Introduction: Personalized medicine based on tumor characteristics is transforming the management of lung cancer. This review provides an overview of clinically approved strategies to personalize treatment for lung cancer as well as evolving strategies in various stages of clinical development. Areas covered: Selecting therapy based on various tumor characteristics such as histology and presence of specific molecular alterations will be covered. This review will not only discuss the role of targeted agents in personalizing care for lung cancer but also the strategies to personalize traditional chemotherapeutic agents. Expert opinion: Advances in genomic medicine to identify key genetic alterations with subsequent development of matching targeted agents are rapidly changing the management of lung cancer. Being able to target key driver molecular aberrations is certainly exciting and clinically meaningful, but only for a limited period of time. Intra- and intertumoral heterogeneity is a major contributor to therapy resistance, a substantial roadblock to durable response. Better understanding of resistance mechanism is at least as important as identifying new targetable genetic changes to effectively advance personalized therapy for lung cancer. Finally, optimization of biopsy specimens and rigorous validation steps to ensure reliability of diagnostic methods would be critical in moving forward.